1990
DOI: 10.1037/0033-2909.107.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in mathematics performance: A meta-analysis.

Abstract: Reviewers have consistently concluded that males perform better on mathematics tests than females do. To make a refined assessment of the magnitude of gender differences in mathematics performance, we performed a meta-analysis of 100 studies. They yielded 254 independent effect sizes, representing the testing of 3,175,188 Ss. Averaged over all effect sizes based on samples of the general population, d was -0.05, indicating that females outperformed males by only a negligible amount. For computation, d was -0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

81
951
21
35

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,338 publications
(1,128 citation statements)
references
References 98 publications
81
951
21
35
Order By: Relevance
“…Of course, change in either direction underscores the malleability of sex differences. Finally, for mathematics, Hyde, Fennema, and Lamon (1990) reported a mean effect size for studies published prior to 1973 of d ϭ 0.31 (boys superior) but only 0.14 for studies since 1974, a decline also found by others (Friedman, 1989).…”
Section: Mean Differences In Broad Cultural Expectations and Contextumentioning
confidence: 61%
See 1 more Smart Citation
“…Of course, change in either direction underscores the malleability of sex differences. Finally, for mathematics, Hyde, Fennema, and Lamon (1990) reported a mean effect size for studies published prior to 1973 of d ϭ 0.31 (boys superior) but only 0.14 for studies since 1974, a decline also found by others (Friedman, 1989).…”
Section: Mean Differences In Broad Cultural Expectations and Contextumentioning
confidence: 61%
“…In contrast to these demonstrations of impressive consistency, there are a number of examples of inconsistency in the gender ratio at the right tail, which are also based on large national samples or meta-analyses (B. J. Becker & Hedges, 1984;Friedman, 1989;Hyde, Fennema, & Lamon, 1990;Linn & Hyde, 1989) The resolution to the question of whether sex differences in math and spatial ability have been consistent or narrowing over time requires consideration of a number of factors, many of which are discussed later. Factors such as (a) the composition of the tests (consistency is more likely when the test content has remained consistent over time, as changes in its composition can lead to shifts in the proportion of problems that favor each sex), (b) changes in the proportions of each sex taking the test, because as one group becomes more numerous in its participation, its scores go down (and there have been increases in female students taking some tests such as the SAT [Nie & Golde, 2008]), (c) changes in analytic approaches, for example, extreme-tail-sensitive approaches versus OLS (see Penner, 2005), and (d) changes in the type and number of math courses each sex has taken (which has occurred; Hyde et al, 2008).…”
Section: Right-tail Differences In Broad Contextual Influencesmentioning
confidence: 99%
“…In healthy adults, the difference between genders showed an advantage of males over females when the level of education is less than four years 18,21 . Never- C1 C2 C3 C4 C5 C6 C7 C8 C9 C10 C11 C12 C13 C14 C15 C16 C17 C18 C19 C20 C21 C22 C23 C24 C25 C26 C27 C28 C29 C30 theless, adults with a higher level of education did not demonstrate any statistically significant difference regarding sex 22 . Therefore, our findings are similar to those described by the authors cited, since there was no difference between genders 17,20 .…”
Section: Discussionmentioning
confidence: 86%
“…Hyde, Fennema, Lamon 1990;Kahle 2004;Chang 2008;Lai 2010;Abubakar, Bada 2012;Eze, Ezenwafor, Obi 2015) focused on differences in performance related to different science subjects. There are many different points of view, a fact which makes it a contested area (Kahle 2004;Penner 2008;Guo, Tsang, Ding 2010).…”
Section: Gender and Academic Achievementmentioning
confidence: 99%